ISOLASI DAN IDENTIFIKASI BAKTERI INDIGEN YANG BERPOTENSI SEBAGAI AGEN BIOREMEDIASI DARI LIMBAH BIOMEDIS CAIR - Wulandhani, Suci; Lohing, Ruben; Hasyim, Ahmad; Misnarliah (Information Technology and Science (ITScience), 2023)
Biomedical waste contains viruses, fungi, toxic chemicals, and radioactive materials. Biomedical waste is dangerous because it is infectious, causing health risks and easily contaminating other wastes if not treated properly. Bioremediation is a method that can be used to treat waste by utilizing indigenous bacteria to remove contaminants. The study aims to determine whether there are isolates of indigenous bacteria that have the potential to be bioremediation agents for liquid biomedical waste in hospitals. The sample comes from a liquid biomedical waste disposal tank at Hasanuddin University Hospital, Makassar. Isolation of bacteria used the pouring method, while identification used the Gram Ziehl Neelson staining method. Pathogenesis was carried out by testing the ability of lactose fermentation and the ability of blood hemolysis. Parameters observed were the morphological and microscopic characteristics of the bacterial isolates, as well as their lactose fermentation ability and hemolytic ability. The results showed that there was one indigenous bacterial isolate from the liquid biomedical waste of Hasanuddin University Hospital Makassar that had the ability to ferment lactose but was unable to hemolyze blood. So that the indigenous bacterial isolate (UH1.2 isolate) was concluded to have a low level of pathogenesis (non-pathogenesis), which is one of the initial characteristics and characteristics of bioremediation agents. Thus, it can be concluded that there is one indigenous bacterial isolate from the liquid biomedical waste of Hasanuddin University Hospital Makassar that has one of the basic characteristics of a bioremediation agent. However, further tests still need to be carried out to ensure that these isolates are those that have the potential to be used as bioremediation agents, namely hydrolytic enzyme activity tests.